Learning-based oviposition constancy in insects - Nataraj, Nandita; Hansson, Bill S.; Knaden, Markus (Frontiers in Ecology and Evolution, 2024)
The search for resources occupies a major part of the time and energy budget of many insects. In this context, many insects display constancy behavior, in which they learn to return to the same, predictably rewarding resource repeatedly. Flower constancy is one such behavior, where nectar-feeding insects restrict foraging visits to a few plant species, sometimes overlooking potentially better-rewarding plants. This phenomenon is well documented in multiple species and is believed to be an optimal strategy to maximize benefits, while minimizing energy and time expenditure. Oviposition constancy is a similar behavior, where insects, dependent on previous experience, restrict their visits to a few types of potential oviposition sites. In contrast to flower constancy, the prevalence of oviposition constancy and the rationale behind this behavior are relatively unknown. An improved understanding of oviposition constancy can act as a lens into the evolutionary history of local insect adaptations, it can help gauge the impact of climate change on insect plant interactions, and it can aid the design of crop-pest management strategies. In this review, we discuss the potential benefits of oviposition constancy in insects and the extent of plasticity occurring in host-plant choice for oviposition.